2017
DOI: 10.36408/mhjcm.v2i3.193
|View full text |Cite
|
Sign up to set email alerts
|

Studi Fenomenologi Pengalaman Keluarga dalam Merawat Pasien Paska Pasung

Abstract: Latar belakang : Pasien pasung yang dirawat di RSJ dan dikembalikan kepada keluarga masih mengalami pemasungan ulang. Tujuan penelitian ini adalah menguraikan pengalaman keluarga dalam merawat pasien paska pasung, menggunakan desain penelitian kualitatif dengan pendekatan fenomenologi. Metode : Teknik pengambilan partisipan menggunakan purposive sampling dengan kriteria inklusi caregiver yang mempunyai anggota keluarga pernah dipasung sebelum dirawat di RSJ dan pernah atau sedang mengalami pemasungan ula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Laila et al [41] reported that PWMD with aggressive or violent behaviour were five times more likely to be subjected to pasung than non-aggressive PWMD. The study by Reknoningsih, Daulima and Putri [50] echoed the above finding and restated that aggressive behaviour led the family to use pasung on more than one occasion with relatives. Other studies confirmed that violence was a reason for the family to use pasung [3,47].…”
Section: Narrative Synthesis Using the Socio-ecological Model Individmentioning
confidence: 77%
See 4 more Smart Citations
“…Laila et al [41] reported that PWMD with aggressive or violent behaviour were five times more likely to be subjected to pasung than non-aggressive PWMD. The study by Reknoningsih, Daulima and Putri [50] echoed the above finding and restated that aggressive behaviour led the family to use pasung on more than one occasion with relatives. Other studies confirmed that violence was a reason for the family to use pasung [3,47].…”
Section: Narrative Synthesis Using the Socio-ecological Model Individmentioning
confidence: 77%
“…Traditional and faith healers remained highly popular despite the routine maltreatment of the mentally ill in their facilities. Caution is suggested when taking a moral perspective on rights and responsibilities in the context of pasung use in this context, as this may be used to justify the maltreatment of people with mental illness, as this research has suggested 35 Reknoningsih (2014) [50] Most caregivers were poorly educated (primary level and not educated). There were five themes: 1.…”
Section: Case Control Studiesmentioning
confidence: 99%
See 3 more Smart Citations